Restless Subjects in Rigid Systems : Risk and Speculation in Millennial Fictions of the North American Pacific Rim. - Wegener, Susanne (transcript Verlag, 2014)
The anticipatory logic of speculation and preemptive politics of risk are increasingly gaining significance in a globalizing neoliberal world. This study traces risk and speculation as aesthetic and political-economic strategies in factual and fictional discourses emerging at the North American Pacific Rim within a decade around 2000. Its exemplary close readings in particular focus on three fictional texts (Kathryn Bigelow's Hollywood film »Strange Days±, 1995, Karen T. Yamashita's novel »Tropic of Orange±, 1997, and Larissa Lai's novel »Salt Fish Girl±, 2002) whose intricate aesthetics pass.
Keywords: American literature -- History and criticism.; American fiction -- Themes, motives.; Risk in literature.; Speculation -- In literature.; Roman américain -- Thèmes, motifs.; Risque dans la littérature.; Spéculation -- Dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM / American / General; American fiction -- Themes, motives; American literature; Risk in literature; Criticism, interpretation, etc.